Elevated suppressor of cytokine signaling‐1 (SOCS‐1): a mechanism for dysregulated osteoclastogenesis in HIV transgenic rats. Issue 1 (10th January 2014) - Lafferty, Mark K.; Fantry, Lori; Bryant, Joseph; Jones, Odell; Hammoud, Dima; Weitzmann, M. Neale; Lewis, George K.; Garzino‐Demo, Alfredo; Reid, William
Abstract Accelerated bone loss leading to osteopenia, osteoporosis, and bone fracture is a major health problem that is increasingly common in human immunodeficiency virus (HIV)–infected patients. The underlying pathogenesis is unclear but occurs in both treatment naïve and individuals receiving antiretroviral therapies. We developed an HIV‐1 transgenic rat that exhibits many key features of HIV disease including HIV‐1‐induced changes in bone mineral density (BMD). A key determinant in the rate of bone loss is the differentiation of osteoclasts, the cells responsible for bone resorption. We found HIV‐1 transgenic osteoclast precursors (OCP) express higher levels of suppressor of cytokine signaling‐1 (SOCS‐1) and TNF receptor–associated factor 6 (TRAF6) and are resistant to interferon‐gamma (IFN‐γ) mediated suppression of osteoclast differentiation. Our data suggest that dysregulated SOCS‐1 expression by HIV‐1 transgenic OCP promotes osteoclastogenesis leading to the accelerated bone loss observed in this animal model. We propose that elevated SOCS‐1 expression in OCP antagonizes the inhibitory effects of IFN‐γ and enhances receptor activator of NF‐kB ligand (RANKL) signaling that drives osteoclast differentiation and activation. Understanding the molecular mechanisms of HIV‐associated BMD changes has the potential to detect and treat bone metabolism disturbances early and improve the quality of life in patients.